2008
DOI: 10.1093/jac/dkn329
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of high vancomycin MIC values among patients with methicillin-resistant Staphylococcus aureus bacteraemia

Abstract: Patients with MRSA bloodstream infections in the ICU or with a history of vancomycin exposure should be considered at high risk of infection with strains for which vancomycin MICs are elevated. Appropriate and aggressive empirical therapy is required for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 11 publications
0
44
0
2
Order By: Relevance
“…In fact, strains of S. aureus with vancomycin MICs as low as 0.5 g per ml by broth dilution or 1 g per ml by standard Etest may produce subpopulations with higher MICs in the VISA/VRSA range (i.e., hVISA). However, despite new evidence from some investigators who believed that a vancomycin Etest MIC of Յ1.5 g per ml may be a better breakpoint for MRSA (184,185), the review pointed out that a further reduction from the current breakpoint of Յ2 g per ml would define 16% of S. aureus isolates surveyed in the United States as being vancomycin intermediate, an outcome out of keeping with current clinical experience (346).…”
Section: Clinical Studiesmentioning
confidence: 98%
See 1 more Smart Citation
“…In fact, strains of S. aureus with vancomycin MICs as low as 0.5 g per ml by broth dilution or 1 g per ml by standard Etest may produce subpopulations with higher MICs in the VISA/VRSA range (i.e., hVISA). However, despite new evidence from some investigators who believed that a vancomycin Etest MIC of Յ1.5 g per ml may be a better breakpoint for MRSA (184,185), the review pointed out that a further reduction from the current breakpoint of Յ2 g per ml would define 16% of S. aureus isolates surveyed in the United States as being vancomycin intermediate, an outcome out of keeping with current clinical experience (346).…”
Section: Clinical Studiesmentioning
confidence: 98%
“…Related to this, some data suggest that low serum levels of vancomycin early in the treatment course of MRSA infections may also be associated with the emergence of VISA and hVISA (48). In studies to determine factors associated with higher vancomycin MICs and the reduced in vitro bactericidal activity of vancomycin against S. aureus (rather than hVISA or VISA per se), prior vancomycin exposure and residence in an intensive care unit (ICU) were independent predictors (185,209).…”
Section: Global Epidemiology and Associated Features Of Hvisa And Visamentioning
confidence: 99%
“…Over the last several years, there have been a number of studies that have demonstrated an association between vancomycin MICs of 1.5 or 2 mg/liter and failure of vancomycin therapy, even though these values lie within the Clinical and Laboratory Standards Institute's (CLSI's) and the FDA's acceptable vancomycin susceptibility range (Յ2 mg/liter). The majority of these reports were derived from patients with MRSA-complicated bacteremia in whom a vancomycin MIC of 1.5 or 2 mg/liter was associated with persistent signs and symptoms of infection, including prolonged days of bacteremia, increased complications, increased lengths of hospital stay, and mortality (4)(5)(6)(7)(8)(9). A recent observational study of 532 patients with MRSA and methicillinsusceptible Staphylococcus aureus (MSSA) bacteremia noted a significantly higher 30-day mortality rate associated with patients who had an isolate for which the MIC exceeded 1.5 mg/liter (by Etest methods).…”
mentioning
confidence: 99%
“…Mortality of people has been increased in instances where the MRSA bacteremia caused by strains with a high vancomycin resistance (MIC >1 μg/mL) and when it was treated empirically either with inappropriate antibiotic or vancomycin [43,44,45]. Avoparcin which is a vancomycin analog, is a glycopeptide antibiotic that can suppress the growth of Gram-positive bacteria and it has been used in livestock feed for growth promotion in broiler chickens, growing pigs, calves and beef cattle.…”
Section: It Was Reported the Development Of Intermediate And High Levmentioning
confidence: 99%